HMGB1 siRNA can reduce damage to retinal cells induced by high glucose in vitro and in vivo - Jiang S; Chen X (Drug Design, Development and Therapy, 2017)
Shuang Jiang, Xiaolong Chen Department of Ophthalmology, Shengjing Hospital of China Medical University, Shenyang, China Background: Diabetic retinopathy (DR), one of the most common complications of late-phase diabetes, is associated with many risk factors, among which continuous low-grade inflammation is one of the principal ones. As such, lowering inflammation levels and maintain the viability of human retinal endothelial cells (HRECs) are critical for DR therapy. HMGB1 is a well-known proinflammatory cytokine. However, whether HMGB1 small interfering RNA (siRNA) can protect retina cells under a high-glucose environment from morphological changes and functional abnormalities remain undetermined. We aimed to investigate the effect of HMGB1 siRNA on retinal cells in DR.Materials and methods: A total of 80 adult Wistar rats were randomly divided into four groups (n=20 each): normal control, diabetes mellitus (DM), scrambled (Scr) siRNA, and HMGB1 siRNA. Rats in the DM, Scr siRNA, and siRNA groups were established by intraperitoneal injection of streptozotocin. At 16 weeks after injection, rats in the siRNA and Scr-siRNA groups were intravitreally injected with 2 µL HMGB1 siRNA and 2 µL Scr-siRNA, while rats in the control and DM groups were intravitreally injected with the same dose of sterile saline. At 1 week after injections, we performed the following experiments. Immunohistochemical staining and real-time quantitative polymerase chain reaction were performed to test HMGB1 protein and messenger RNA expression in retinas. We performed TUNEL assays to detect retinal cell apoptosis and electroretinography to detect retinal function. In HRECs treated with high glucose, proliferation, morphology, apoptosis, superoxide dismutase (SOD), and reactive oxygen species production were detected. Western blot was applied to determine the expressions of HMGB1 and its related protein and apoptosis protein.Results: Intravitreal injection of HMGB1 siRNA reduced protein and messenger RNA expression of HMGB1 (both P<0.05). Intravitreal injection of HMGB1 siRNA reduced apoptosis of retinal cells (P<0.05), protected morphological changes in the retina, and improved the function of the retina (P<0.05). In HRECs treated with high glucose, HMGB1 siRNA pretreatment increased cell viability, reduced cell apoptosis, and reduced oxidative damage to cells (all P<0.05). Western blot detection found that HMGB1 siRNA pretreatment can inhibit the expression of cleaved caspase 3 and improve the expression of BCL2 (P<0.05). HMGB1 and NFκB expression increased in a time-dependent manner in the high-glucose environment and IKKβ and NFκB protein expression decreased significantly after HMGB1 silencing.Conclusion: As a therapeutic target, HMGB1 siRNA can reduce retinal cell damage induced by high glucose in vitro and in vivo and delay DR progress through the HMGB1–IKKβ–NFκB signaling pathway. Keywords: diabetic retinopathy, small interfering RNA, human retinal endothelial cells, high-mobility group box 1, inhibitor of nuclear factor κB, nuclear factor κB